(untitled) (Research, Society and Development, 2020)
Objective: To analyze the contributions of remote teaching-learning strategy to the work process of community health agents in the context of COVID-19. Method: This is an account of the experience lived by master’s students when carrying out a health education action for community health agents in remote mode. This study arises from the elaboration of a lesson plan, an activity originating from the discipline of teaching and learning process in health sciences of the master of the graduate program in nursing and health at the State University of Southwest Bahia. Results: The educational health action for community agents, in the virtual mode during the pandemic, constitutes a strategy for training and sharing knowledge, in view of the agents ’positive responses, although the agents’ adherence to training has been low. Conclusion: Remote action enabled the exchange of experience and resolved doubts regarding the actions carried out on a daily basis, making it possible for the team to get closer, at the moment of social distance, however, strategies are needed to reach a greater number of participants in a virtual way.